2022
DOI: 10.1111/ene.15385
|View full text |Cite
|
Sign up to set email alerts
|

Natural history and burden of Huntington's disease in the UK: A population‐based cohort study

Abstract: Background Huntington's disease (HD) is a rare neurodegenerative disease that presents with progressive psychological, cognitive and motor impairment. These diverse symptoms place a high burden on the patient, families and the healthcare systems they rely on. This study aimed to describe the epidemiology and clinical burden in individuals with HD compared with controls from the general population. Methods This cohort study utilised data from general practitioner medical records to estimate the prevalence and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
3
3
0
Order By: Relevance
“…Data were broadly comparable in the two databases. Recorded HD incidence and prevalence was slightly higher in CPRD GOLD but trends were very similar in both databases and highly consistent with previous estimates 37–39. Incidence of common cancers showed somewhat different trends in the two databases between 1990–2000, but was remarkably similar thereafter and was consistent with national reference rates, particularly when primary care and linked secondary care and mortality data were combined.…”
Section: Discussionsupporting
confidence: 87%
“…Data were broadly comparable in the two databases. Recorded HD incidence and prevalence was slightly higher in CPRD GOLD but trends were very similar in both databases and highly consistent with previous estimates 37–39. Incidence of common cancers showed somewhat different trends in the two databases between 1990–2000, but was remarkably similar thereafter and was consistent with national reference rates, particularly when primary care and linked secondary care and mortality data were combined.…”
Section: Discussionsupporting
confidence: 87%
“…The long follow-up time and complete death recording make this an ideal study to assess mortality in patients with a diagnosis of HD. The median survival time in the AoHD cohort was 12.1 years, which is similar to recent population-based cohort studies of HD in Israel (12 years [42]) and the UK (12.4 years [47]), which also define the index as the first diagnosis in the patient's medical records and take place during a similar time window. Other studies have reported median survival up to 25 years [48][49][50] which may be attributable to the index definition, study methods and accuracy of death reporting.…”
Section: Discussionsupporting
confidence: 81%
“…The impact of HD on patients and their family members is significant [ 3 5 ]. According to a cohort study of medical records of primary care patients in the United Kingdom, a significantly higher relative risk of psychotic disorders, depression, insomnia, dementia, weight loss, pneumonia, and falls was observed in patients with HD compared with the demographically matched general population [ 4 ]. Despite the well-documented substantial disease burden of HD, the benefits of currently available treatments are limited to the management of motor and psychiatric symptoms.…”
Section: Introductionmentioning
confidence: 99%